CHARGING AND DETECTION OF MESOSPHERIC DUST WITH INSTRUMENT SPID ON G-CHASER ROCKET - Gunnarsdottir, Tinna; Trollvik, Henriette; Mann, Ingrid; Olsen, Sveinung viggo; Eilertsen, Yngve; Antonsen, Tarjei; Björk, Arne; Restad, Erlend; Havnes, Ove; Fredriksen, Åshild; Boothby, Christoffer; Hansen, Rikke Hedelund; et al. (European Space Agency (ESA), 2019)
The Smoke Particle Impact Detector (SPID) was ﬂown on the G-Chaser student rocket that was launched from Andøya on 13 January 2019. SPID is a Faraday cup instrument with applied bias voltages to deﬂect the ambient plasma and a target area inside the probe designed to measure the dust particles by charge detection. The charging process of the dust particles in the detector is important for interpretation of the measurements and the inﬂuence of the charging models is discussed. Preliminary analysis of the SPID observations shows that ambient plasma and sunlight had an inﬂuence on the signals; further analysis is needed to retrieve information on impacting dust from the data.